Aerosol-to-liquid collection: A method for making aqueous suspension of hydrophobic nanomaterial without adding dispersant. Issue 10 (3rd October 2017) - Iida, Kenjiro; Ehara, Kensei; Takahashi, Kayori; Sakurai, Hiromu; Nakanishi, Junko; Yamamoto, Kazuhiro; Gamo, Masashi
ABSTRACT: This article introduces an aerosol-based technique to make aqueous suspension of hydrophobic nanomaterial without adding dispersant. The method is intended for making a test-sample for evaluating the toxicities of nanomaterial by intra-tracheal administration. The method can wet the surface of hydrophobic nanomaterial within a few seconds. After the wetting process five to ten minutes of sonication assisted with manual stirring can fully disperse the hydrophobic nanomaterials in water. Two types of TiO2 nanomaterial were used in this study; Tayca JMT-150IB whose surfaces are coated with negatively charged hydrophobic functional group, and P25 whose surfaces are naturally hydrophilic. Nanomaterials are aerosolized by a dry-method and become micrometer-sized agglomerates. Then supersaturated water vapor is condensed onto these airborne agglomerates by using a growth tube collector. The collected suspension (CS) of hydrophobic nanomaterial (JMT-150IB) is prepared in two steps; airborne agglomerates are collected onto a flat surface then transferred to liquid-water and subsequently sonicated for complete dispersion. This method works equally well for making the CS of hydrophilic nanomaterial. Size distribution measurements of the CS show that airborne agglomerates of TiO2 dissociate into smaller units of agglomerates once they are captured into water, and the sizes of the agglomerates are in the nanometer to sub-micrometer range. Light scattering technique is used to show that a short sonication process can reproduce the particle number concentration of the CS after long storage. Copyright © 2017 American Association for Aerosol Research